A prospective study of the Various Categories of Crown to Root Ratio of Premolars by Using Cone Beam CT Images - Haseeb Ahmad, Umar Nasir, Mahwish Zeb, Asma Ali, Asfandyar Qureshi, Sana Naeem (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cone beam computed tomography (CBCT) has gained worldwide acceptance in the field of dentistry, because it provides definite images in the form of slices of single roots which can accurately measure the crown and root lengths of all the teeth including premolars. Crown and root lengths have its applications in surgical extrusion and crown lengthening in cases of tooth wear. Aim: To document the frequency of crown-root ratio (using CBCT images) in longitudinal section of the premolar teeth. Study design: Descriptive cross-sectional study. Place and duration of study: Department of Radiology, Khyber College of Dentistry and Hospital, Peshawar and Department of Radiology, Sardar Begum Dental College and Hospital Peshawar from 1st January 2020 to 30th June 2020. Methodology: One hundred and thirty five patients of both the genders were selected by obtaining there CBCT images. A written informed consent was taken from the patients or their attendants through concerned dentist who advised CBCT. Data of crown root ratio of premolar teeth were recorded in the form of categorical variables (crown and root length). Results: The mean age was 29.64±4.47 years. The highest frequency of patients was of 28(14.8%) years and 29(17%) years. There were 87(64.4%) males while 48(35.5%) females. Conclusion: There is significant difference of crown root ratio between the premolars of maxilla and mandible and the right and left quadrants of both arches. Key words: Cone beam computed tomography (CBCT), crown-to-root ratio (CRR), Premolar